Formation of extracellular traps by circulating neutrophils and monocytes in rheumatoid arthritis patients: a study of new citrullinated autoantigen - S. A. Bedina (SPb RAACI, 2021)
Detection of subcellular structures containing typical citrullinated rheumatoid autoantigens in a single compartment presents a special interest, due to importance of anticitrulline autoantibodies for the autoimmune response in RA. Neutrophil and monocyte extracellular traps (NETs and ETs, respectively) may be considered such candidate structures. Our objective was to assess ability of blood neutrophils and monocytes from RA patients to generate NETs and ETs spontaneously and after in vitro induction.32 patients with verified RA and 30 healthy volunteers as controls were included into the study. Circulating neutrophils and monocytes were isolated with one-step density gradient centrifugation using three layers of ficoll-amidotrizoate gradient. Composition of isolated cellular fractions, their viability, and non-specific activation were evaluated microscopically using Trypan Blue exclusion test, as well as Nitro-Blue Tetrazolium test. The NETs were induced by phorbol-12-myristate-13-acetate, and ETs by bacterial LPS. Spontaneous and induced formation of extracellular traps was assessed using fluorescence microscopy. Neutrophil and monocyte fractions contained minute percentages of impurities and low extents of activated and dead cells. Spontaneous NET and ET formation in RA patients was significantly increased comparing to healthy controls. Neutrophils from ACPA-positive RA patients were found to have higher frequency of NET formation, compared to ACPA-negative RA patients. The monocytes did not demonstrate such differences between these subgroups. There were no substantial morphological differences in NETs and ETs patterns between the individuals from both groups. Induced extracellular trap production in RA was significantly higher compared to healthy controls. The level of myeloperoxidase-specific fluorescence in ETs was considerably lower than in NETs. NETs could probably be considered as a source of citrulline autoantigen participating in autoantibody production and stimulation of inflammatory autoimmune responses in RA, whereas ETs may play less important role in this process.